Arsitektur berkelanjutan: Belajar dari ume kbubu, rumah tradisional masyarakat Fatumnasi - Apridus Kefas Lapenangga; Donatus Ara Kian; Benediktus Boli (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Ume kbubu, as the traditional house of the Fatumnasi community, is a cultural product from local wisdom which has continually been adapted to the environment to ensure its sustainability. This research was, therefore, conducted to explore the principles of sustainable architecture in ume kbubu using an explorative approach with an ethnographic design applied to obtain necessary information from the objects of study such as the houses of the Village Head and the leader of Hamlet 1 in Fatumnasi village which were determined using a purposive sampling technique. The data were obtained through observation, interviews, and literature study and the results showed the ume kbubu’s sustainability is due to its long adaptation and natural selection for years which makes it a sustainable architecture and was also found to fulfill the three elements required which are economic, social and environmental.